Part I. Palladium-catalysed C-glycosylations. Part II. Synthesis of indolizines via intramolecular C-N bond formation - Leng, Wei Lin (2017)
Allyl moiety can be commonly found in organic compounds. It serves as key intermediate in chemical reactions and can be stabilised by resonance. This thesis focuses on exploiting the allylic functionality in both sugar system and other organic compounds to bring about bond formation efficiently. In the first chapter, a brief introduction of the various types of allylic systems will be covered. Allylic cation will be the main focus and methods to generate this allylic cation using palladium catalyst as well as reactions of this allylic cation will be discussed. In particular, a specific allylic system, glycal, which can generate π-allyl palladium species, will be highlighted. In the second chapter, a one-pot synthesis of C-vinyl glycosides via palladiumcatalysed decarboxylative allylation/Wittig reaction is described. The nucleophilic phosphorus ylide attacks π-allyl palladium species generated in situ, which can undergo subsequent Wittig reaction upon deprotonation.This methodology can form di- and trisubstituted alkenes in good β-anomeric stereoselectivities. Depending on the aldehydes’ coordinating ability, opposing olefin selectivities can be obtained. In the third chapter, C-glycosylation by adopting a dual catalytic system with Ir photocatalyst and Pd catalyst is demonstrated. The π-allyl palladium species generated in situ undergoes single electron reduction to form an allylic radical, which then quickly couples with another radical. This methodology showcases the utility of radical-radical coupling to achieve stereoselective α-C-glycosides. In the last chapter, based on our previous understanding of allylic systems, an application to non-sugar system is attempted in the hope of obtaining bioactive Nheterocycles, which are commonly found in pharamaceutical products. The activation by electrophilic reagent results in π-allylic cation formation and subsequent cyclisation occurs to furnish multisubstituted indolizines. This methodology can lead to C-N bond formation and the multisubstituted indolizines can be utilised in further structure-activity relationship studies.